A Conversation Beyond Words: Exploring Somatic Countertransference When Working With Alexithymic Clients - Mercado, Gabriela (Auckland University of Technology, 2006)
This study investigates the impact that the unconscious, non verbal communication of the client with minimal language for feelings has on the body of the therapist and the response that this impact generates in the therapist. This client group is commonly defined as alexithymic, which refers to people who lack words to express emotions, have poor phantasy and recite facts and daily realities with no connection to their internal world. The findings of this study support the idea that clients with alexithymia can communicate their feelings in a non-verbal way which is perceived by the therapist through the somatic aspect of the countertransference. The findings within this research also show that many psychotherapists experience somatic countertransference at some point. Surprisingly, not many psychotherapists have described how these experiences are incorporated within the clinical practice. There is a gap in the literature as little has been written in this area. This presents a difficulty in exploring and acknowledging the bodily feelings of the therapist in the therapy session. Two main uses of somatic countertransference were identified from the research. Firstly, the therapist disclosing what was felt in her/his body. Secondly, the use of somatic responses as a source of information that helps the therapist in the construction of metaphors. Both of these uses of addressing somatic countertransference contribute to further exploration of unspoken feelings. This is particularly important when working with alexithymic clients as one of their main traits is the struggle to verbally express their feelings. This dissertation uses a modified systematic literature review with clinical vignettes to investigate how therapists experience and use their somatic responses within their practice.
Keywords: Countertransference (Psychology); Alexithymia -- Treatment